2010
DOI: 10.1002/mds.22939
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the burden experienced by spousal caregivers of individuals with Parkinson's disease

Abstract: Although previous research has attempted to identify the needs of caregivers for individuals with Parkinson's disease (PD), most has focused on the demands associated with the physical needs of the patient, and not on "mental burden." This study used the repertory grid method to capture the full range of caregivers' subjective experience, quantify their perceptions, and to acquire information that might be useful in directing remediation attempts. Within this sample, caregivers reported far greater burden from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…The caregiver study results indicated that the quality of the caregiver-veteran relationship was significantly related to stress levels; this finding was also supported by other researchers [19,20] . The duration of caregiving was predictably associated with daily hours spent in caregiving but not with stress levels.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The caregiver study results indicated that the quality of the caregiver-veteran relationship was significantly related to stress levels; this finding was also supported by other researchers [19,20] . The duration of caregiving was predictably associated with daily hours spent in caregiving but not with stress levels.…”
Section: Discussionsupporting
confidence: 77%
“…After a review of validated PD caregiving instruments [1,15,18,20] , the researchers found none that integrated all the required components for this study. The preferred survey was one devised for a mailed caregiver study, contained specific questions unique to this sample of participants, and was simple and short in design so that caregivers would be more likely to complete the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Caregiver interventions include educating the caregiver about the effects of PD, training the caregiver in the specific skills needed to support the patient, provide information about relevant aids and adaptations that may reduce caregiver burden, and empower the caregiver to maintain or reacquire a healthy balance between personal activities and caring [50,103,119]. In a trial about homebased OT, the participating PwP, caregivers and therapists reported the benefits of actively involving the caregiver in the intervention [60].…”
Section: Advice For and Training Of The Caregivermentioning
confidence: 99%
“…In addition, when there is a marital or family relationship between the caregiver and the individual with PD, both may experience minor social deaths, which can begin in the work environment, with colleagues and friends, and even reach the family context 19 .…”
Section: Discussionmentioning
confidence: 99%